2020
DOI: 10.1111/jfpe.13632
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and optimization of drying conditions of dog rose for preparation of a functional tea

Abstract: Dog rose (Rosa canina L.) is a rosehip used for domestic and industrial purposes. It has great antioxidant compounds such as lycopene and phenolic compounds. In the present study, technological processing was investigated to formulate a functional tea with great nutraceutical compounds. The drying conditions were optimized to have maximum antioxidant properties. The optimum conditions were 68°C and 1 m s−1, providing the values of 40751.17 mg GAE/kg, 14.17 mg EGC E/100 g, 278.87 mmol TE/g, 44.62 mmol ISE/g, 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 49 publications
2
15
2
Order By: Relevance
“…It was observed that the dependent variables responded differently with each combination of independent variables. Such observation was observed previously during the optimization for the extraction conditions [ 31 , 38 ]. The significance of regression coefficients of polynomial models was set at p < 0.05.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…It was observed that the dependent variables responded differently with each combination of independent variables. Such observation was observed previously during the optimization for the extraction conditions [ 31 , 38 ]. The significance of regression coefficients of polynomial models was set at p < 0.05.…”
Section: Resultssupporting
confidence: 83%
“…No quadratic and interaction units showed substantial impacts on the responses. Previously, it was demonstrated that the RSM linear and quadratic terms react differently depending on the samples’ intrinsic characteristics, many independent variables, and analysis conditions [ 32 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…These findings indicated that the models were well-fitted to the rehydration data of autumn olive. Similarly, these models had successfully applied to predict rehydration of fruits and vegetables (Benseddik et al, 2019;Ghellam & Koca, 2020;Noshad et al, 2012;Pashazadeh et al, 2021). The best fitted model was found to be the Peleg model, followed by Weibull and Vega-galves models.…”
Section: Rehydration Curves and Modelingmentioning
confidence: 98%
“…The one-factor design was applied to investigate the effect of drying temperature on TPC, LC, FRAP and total color change (ΔE) of autumn olive ( (Koca et al, 2009;Pashazadeh et al, 2021). The regression coefficients of polynomial models are significant at p ≤ .05.…”
Section: Analysis Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation